Czy alternatywne metody głosowania i inne ułatwienia wyborcze mogą rozwiązać problem przymusowej absencji wyborczej? Refleksje i spostrzeżenia osoby niepełnosprawnej w świetle wyborów samorządowych 2014 - Jankowska, Magdalena (Polityka i Społeczeństwo, 2021)
The fundamental claim which accompanied the implementation of alternative voting methods into the Polish Law was the guarantee of the fullest realization of the universal suffrage. The current regulations of the Electoral Code allow people with disabilities to vote by mail or by proxy. This deviation from the rule of voting personally in a polling station and enfranchising people with disabilities is a clear sign of the adaptation of Polish reality to Western European standards. The enactment of the law and implementation of additional legal solutions are only the first step to a greater change. The current challenges of electoral law are both perfecting the new voting methods and educating voters to compel them to vote; that is to exercise their constitutional privilege.